Mode I fracture evaluation of CFRP-to-concrete interfaces subject to aggressive environments agents: Freeze-thaw cycles, acid and alkaline solution - Wang, Xiaomeng; Petrů, Michal (Composites. Part B, Engineering, 2019)
The long-term durability of the interface between FRP (fiber reinforced polymer) and concrete is crucial to the safety of FRP strengthened concrete structures. Some experimental works have been carried out to investigate the effect of environmental factors on model II fracture behavior of the FRP-to-concrete interface. However, fewer efforts have been made to estimate interfacial durability under mode I loading. This study evaluates the mode I fracture energy release rate of CFRP (carbon fiber reinforced polymer)-to-concrete interface subjected to freeze-thaw cycling, acid attack, and alkali attack. Significant decrease of fracture energy release rate is observed after environmental conditioning. With the increase of freeze-thaw cycles and soaking time, the failure mode of the specimen changes from tensile failure of concrete to adhesive failure along the interface. Test results also confirm that the durability of the CFRP-to-concrete interface can be improved by application of silane coupling agent under freeze-thaw cycling and alkaline condition.